The 2021 proposal to increase market forces in the Australian residential aged-care sector. (January 2023) - Cutler, Henry; Gu, Yuanyuan; Bilgrami, Anam; Partington, Andrew
Highlights: Australia will introduce market reforms to increase nursing home care quality. Consumers will get more quality information to help choose a provider. Providers will be more easily able to compete for consumers. Care prices must increase for providers to substantially increase quality. Supported choice and investment to improve care models is also needed. Abstract: In Australia, the US and Europe, policy makers use markets to incentivise aged care providers to produce greater quality care. The Australian Government announced in 2021 that it would further increase market forces in residential aged care to improve quality. The proposals respond to poor quality found within residential aged care, with overuse of psychotropic medications and physical constraints, social isolation and neglect. This paper outlines the market-orientated reforms the Government seeks to implement, including the policy development pathway over the last two decades. It refers to a theoretical model of provider behaviour under administered prices, and empirical research on the impact of similar market-orientated reforms delivered elsewhere, to highlight the reforms' strengths, weaknesses, and potential market outcomes. This paper concludes by identifying additional reforms that could better incentivise care quality and offers lessons to countries that have sought to marketise their nursing home care sectors.